Prevalence of Asthma in Ciamis Regency, West Java: Asthma - Nurfita; Reva Afra; Restiani; Najwa Rezky Kurniawan; Muhammad Luthfy Mangku (Journal of Health Science and Pharmacy, 2026)
Background: Asthma is a chronic respiratory disease with a rising global prevalence, including in Indonesia. In Ciamis Regency, West Java, asthma has become a significant health concern due to the high incidence of cases and insufficient public awareness regarding triggering factors and preventive measures. Environmental factors such as an unhealthy living environment, smoking habits, and exposure to air pollution are common but often overlooked causes of asthma exacerbation. Objective: This study aims to assess the prevalence of asthma in Ciamis Regency and identify the various risk factors associated with the condition through a systematic review of relevant literature. Methods: This study employs a quantitative descriptive approach. Secondary data for the analysis were sourced from the Ciamis Regency Health Profile, published by the Ciamis Regency Health Office. The collected data include the number of asthma cases in the region, which were utilized to assess the prevalence and distribution of asthma in Ciamis Regency. Results: The findings revealed that the prevalence of asthma in Ciamis Regency is significantly influenced by environmental factors, including air pollution from cigarette smoke and burning, damp housing conditions, and unhealthy lifestyles. Additionally, genetic predisposition, psychological stress, and limited access to medical treatment were identified as major triggers. Low health literacy among the population further exacerbates the management and control of asthma. Conclusion: To effectively reduce the prevalence of asthma in Ciamis Regency, a collaborative effort involving local governments, healthcare professionals, and the community is essential. Emphasizing promotive and preventive measures, enhancing health education, and improving environmental conditions are crucial strategies for sustainable asthma management. Keywords: Asthma, Prevalence, Risk Factors, Ciamis Regency